Research on Determinants of Loan Loss Provisions in Chinese Commercial Banking Sector From 2012 to 2016 - Junshan, Chen (2017)
This dissertation adopts a panel dataset of 185 commercial banks from the period of 2012 to 2016 to analyse the determinants of the loan loss provisions and test the hypotheses relating to the LLPs in this context. Both capital management hypothesis and income smoothing hypothesis have been proved in this research, and pro-cyclicality of LLPs has been found. Furthermore, regional effects and cost efficiency have been considered in this model.